2016
DOI: 10.1128/jvi.01756-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Monoclonal Antibodies That Bind to Different Epitopes of the 2009 Pandemic H1N1 Influenza Virus Neuraminidase

Abstract: Antibodies against the neuraminidase (NA) of influenza virus correlate with resistance against disease, but the effectiveness of antibodies against different NA epitopes has not been compared. In the present study, we evaluated the in vitro and in vivo efficacies of four monoclonal antibodies (MAbs): HF5 and CD6, which are specific to two different epitopes in the NA of 2009 pandemic H1N1 (pH1N1) virus, and 4E9 and 1H5, which are specific to a conserved epitope in the NA of both H1N1 and H5N1 viruses. In the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
(62 reference statements)
2
59
0
Order By: Relevance
“…The NA protein is essential for release of virus particles from infected cells and decoy receptors (e.g., in mucus) and for preventing virion aggregation. The NA protein is also an important target of the immune response and antiviral drugs (1)(2)(3). The IAV NA protein appears, however, understudied compared to the HA protein.…”
mentioning
confidence: 99%
“…The NA protein is essential for release of virus particles from infected cells and decoy receptors (e.g., in mucus) and for preventing virion aggregation. The NA protein is also an important target of the immune response and antiviral drugs (1)(2)(3). The IAV NA protein appears, however, understudied compared to the HA protein.…”
mentioning
confidence: 99%
“…These antibodies all bind to Cal09 NA and inhibit NA catalytic activity to varying degrees. HF5 and CD6 are strain-specific antibodies that each target distinct epitopes, and strongly inhibit NA activity as measured by ELLA [5]. Antibodies 1H5 and 4E9 recognize a similar epitope on the lateral surface of the NA head that is conserved across the N1 subtype, but these antibodies only weakly inhibit NA activity in ELLA assays [5].…”
Section: Anti-na Monoclonal Antibodies Neutralize a Na-binding-dependmentioning
confidence: 99%
“…NA also plays an important role in vivo by helping the virus penetrate mucus barriers to reach target cells [2,3]. Because only HA is needed for viral entry, anti-NA antibodies are not strongly neutralizing in infection assays where viruses are only allowed to undergo a single cycle of growth [4,5]. However, many studies have shown that anti-NA antibodies are associated with reduced disease severity in humans [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of these mAbs are directed against various epitopes contained within the HA surface protein while one targets the matrix protein 2 (M2). In addition to the HA and M2, anti-neuraminidase (NA) mAb have also proven to be protective in the mouse model but, to our knowledge, have yet to enter clinical development (Doyle et al, 2013; Jiang et al, 2015; Shoji et al, 2011; Wan et al, 2013; Wohlbold et al, 2016; DiLillo et al, 2016). One potential concern regarding mAb as antivirals include the possibility that their use may drive the evolution of viral escape mutations which could be resistant not only to the mAb but to natural or vaccine-induced immunity.…”
Section: Introductionmentioning
confidence: 99%